Transition metal-substituted lead halide perovskite absorbers. Issue 7 (27th January 2017) - Sampson, M. D.; Park, J. S.; Schaller, R. D.; Chan, M. K. Y.; Martinson, A. B. F.
Abstract : Cobalt substituted MAPbBr3 films are a novel perovskite material with tunable mid-gap density of states providing promise for IB photovoltaics. Abstract : Lead halide perovskites have proven to be a versatile class of visible light absorbers that allow rapid access to the long minority carrier lifetimes and diffusion lengths desirable for traditional single-junction photovoltaics. We explore the extent to which the attractive features of these semiconductors may be extended to include an intermediate density of states for future application in multi-level solar energy conversion systems capable of exceeding the Shockley–Queisser limit. We computationally and experimentally explore the substitution of transition metals on the Pb site of MAPbX3 (MA = methylammonium, X = Br or Cl) to achieve a tunable density of states within the parent gap. Computational screening identified both Fe- and Co-substituted MAPbBr3 as promising absorbers with a mid-gap density of states, and the later films were synthesized via conventional solution-based processing techniques. First-principles density functional theory (DFT) calculations support the existence of mid-gap states upon Co incorporation and enhanced sub-gap absorption, which are consistent with UV-visible-NIR absorption spectroscopy. Strikingly, steady state and time-resolved PL studies reveal no sign of self-quenching for Co-substitution up to 25%, which suggest this class of materials to be a worthy candidate for future application in intermediate band photovoltaics.